Supporting Science-Based Agricultural Biotechnology Policy Coordination, Education, and Capacity Building - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2023)
Descripción: Creating spaces for analysis, debate, and sharing knowledge related to biotechnology as an added value for the agricultural and livestock and agricultural sector within its production processes are methodologies for building opportunities that will allow greater scope in the market positioning of this agricultural industry. Thus, this project seeks to raise awareness of the importance of including biotechnology in production, as part of the innovation and adaptation necessary for greater business competitiveness. It also seeks to make visible the real needs of the sector, to provide a debate that generates a solution for change through the technical support provided by the experience of implementing biotechnology in crops. Objetivo General: To improve understanding of specific issues to be discussed at COP-MOPs and support participation of delegations of selected LAC countries.